73.9k views
0 votes
1.x(x+4)=5

2.(x+3)raise to 2=36
3.(t+2)raise to 2+(t-3)raise to2 =9
4.3 4
--+-- =x-1
x 2x
5. 3 4
-------+------- =x-1
m-2 m+5
how did you transform each equation into a quadratic equation what concepts or principles did you employ​

User Avshalom
by
5.6k points

1 Answer

6 votes

x (x + 4) = 5

x² + 4x = 5

x²+ x + (-5) = 0

(x+3)²+(t+3)²=9

x² + 6x + 9 + t² + 6t + 9 = 9

x² + t² + 6x + 6t + 18 + (-9) = 0

x² + t² + 6x + 6t + 9 = 0

x² + t² + 6(x + t) + 9 = 0

3/x + 4/2x = x - 1

6/2x + 4/2x = x - 1

10/2x = x - 1

10 = (x - 1) 2x

10 = 2x² - 2x

0 = 2x² + (-2x) + (-10)

User Pjhsea
by
5.9k points